Relations of vitamin D status, gender and type 2 diabetes in middle-aged Caucasians - Stadlmayr, Andreas; Aigner, Elmar; Huber-Schoenauer, Ursula; Niederseer, David; Zwerina, Jochen; Husar-Memmer, Emma; Hohla, Florian; Schett, Georg; Patsch, Wolfgang; Datz, Christian (Acta Diabetologica, 2015)
Vitamin D (Vit D) deficiency may be linked to the development of obesity-associated complications such as insulin resistance and type 2 diabetes. We therefore evaluated the relationship of Vit D serum concentrations with metabolic parameters and type 2 diabetes in middle-aged Caucasian men and women. One thousand six hundred and thirty-one Caucasians (832 males, 58.8 ± 9.7 years; 799 females, 59.7 ± 10.7 years) were evaluated in a cross-sectional study. Vit D status was assessed by measuring the serum concentration of 25-hydroxyvitamin D3 [25(OH)D3]. Type 2 diabetes prevalence was ascertained by medical history, fasting plasma glucose concentrations, oral glucose tolerance testing and/or glycosylated hemoglobin. Men displayed higher crude or seasonally adjusted 25(OH)D3 serum concentrations than women (24.64 ± 10.98 vs. 22.88 ± 11.6 ng/ml; P < 0.001). Strong associations between body mass index (BMI) and 25(OH)D3 were observed in both genders (P < 0.001). Seasonally adjusted levels of 25(OH)D3 revealed stronger associations with type 2 diabetes in women than men (P < 0.001). However, adjustment for BMI and other confounding variables revealed an independent inverse association of 25(OH)D3 with diabetes only in women (P < 0.001), whereas the association was abrogated in men. Using a 15 ng/ml 25(OH)D3 cutoff for binary comparison, adjusted odds ratios for having newly diagnosed or known type 2 diabetes more than doubled (2.95 [95 % CI 1.37-4.89] and 3.26 [1.59-6.68], respectively), in women below the cutoff. We conclude that in women, but not in men, low 25(OH)D3 serum levels are independently associated with type 2 diabetes. These findings suggest sex-specific effects of Vit D in the pathogenesis of type 2 diabetes.
EVALuna2:12976